PENGARUH pH DAN TEMPERATUR TERHADAP KESTABILAN AKTIVITAS XILANASE DARI Trichoderma viride - Kusuma, Sicilia; Sutrisno, Sutrisno; Indahyanti, Ellya (Jurusan Kimia, FMIPA Universitas Brawijaya, 2013)
Xylanase is an enzyme that can hydrolyze xylan into reducing sugar xylose and xilo-oligosaccharides. The research was carried out to determine the effect of pH and temperature on stability of xylanase activity of T. viride . Its effects were observed by measuring the residual activity after the enzyme xylanase was incubated for 9 hours at pH variation (4, 5, 6) and the variation of temperature (50, 60, 70 oC ). Enzyme activity is said to be stable if the remaining activity is greater than or equal to 50%. Xylanase activity was determined by measuring the levels of reducing sugars produced during the enzymatic reaction, by spectrophotometry using DNS reagent. The results showed that the xylanase activity remained stable after the enzyme was incubated for 9 hours at pH 4, 5, 6 and at temperatures of 50, 60, 70 oC. The stability of xylanase activity is highest when xylanase was incubated at pH 5 and temperature 60 ° C.Key words: enzyme stability , pH, temperature , Trichoderma viride, xylanase.